Caracterização e estudo da corrosão do amálgama dentário dispersalloy por meio das técnicas de polarização potenciodinâmica e espectroscopia de impedância - Acciari, Heloísa Andréa [UNESP]; Guastaldi, Antonio Carlos [UNESP]; Tremiliosi Filho, Germano [UNESP] (My University, 1997)
The corrosion of dental amalgam in aqueous media was interpreted by means of a.c. impedance techniques and anodic polarization. The Nyquist and Bode diagrams are influenced by the porous structure of the amalgams, the surface film formation and the adsorption of intermediates. In general, the impedance spectra are rather complex and very difficult to interpret. The Dispersalloy amalgam (high copper, dispersion type alloy) was characterized by scanning electron microscopy and energy dispersive X ray analysis. The chemistry analysis was determined by atomic absorption spectrophotometry. Although high copper amalgams as a group show superior physical properties and clinical performance to low copper amalgams, a high copper content does, not necessarily mean improved clinical performance. Nevertheless, they too, corrode in the mouth.
Characterization and corrosion study of the Dispersalloy dental amalgam by impedance techniques and anodic polarization
Keywords: Anodic polarization; Corrosion; Dental amalgam; Dispersalloy; Impedance